2015
DOI: 10.1002/2014ja020809
|View full text |Cite
|
Sign up to set email alerts
|

Dayside reconnection under interplanetary magnetic field By‐dominated conditions: The formation and movement of bending arcs

Abstract: Based upon a survey of global auroral images collected by the Polar Ultraviolet Imager, Kullen et al. (2002) subdivided polar cap auroral arcs into a number of categories, including that of “bending” arcs. We are concerned with those bending arcs that appear as a bifurcation of the dayside auroral oval and which subsequently form a spur intruding into the polar cap. Once formed, the spur moves poleward and antisunward over the lifetime of the arc. We propose that dayside bending arcs are ionospheric signatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…This model was augmented by Milan et al (2005) to show how magnetotail reconnection within a twisted tail (B Z > 0, B Y ≠ 0) could give rise to tongues of closed magnetic flux intruding into the polar cap from the nightside to form transpolar arcs. Carter et al (2015) explained how low-latitude magnetopause reconnection occurring for B Y -dominated IMF (B Z ≈ 0, B Y ≠ 0) gives rise to a class of polar cap auroras known as bending arcs. We have now elucidated the dynamics during purely northward IMF, completing our understanding of the ECPC response of the magnetosphere to solar wind coupling under all IMF clock angle regimes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was augmented by Milan et al (2005) to show how magnetotail reconnection within a twisted tail (B Z > 0, B Y ≠ 0) could give rise to tongues of closed magnetic flux intruding into the polar cap from the nightside to form transpolar arcs. Carter et al (2015) explained how low-latitude magnetopause reconnection occurring for B Y -dominated IMF (B Z ≈ 0, B Y ≠ 0) gives rise to a class of polar cap auroras known as bending arcs. We have now elucidated the dynamics during purely northward IMF, completing our understanding of the ECPC response of the magnetosphere to solar wind coupling under all IMF clock angle regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Østgaard et al, 2003). "Bending arcs" are auroral features that protrude into the polar cap from the dawnside or duskside auroral oval and progress over time toward the nightside, which are now thought to be created by low-latitude magnetopause reconnection, in a manner similar to poleward-moving auroral forms associated with flux transfer events, during B Y -dominated IMF (Carter et al, 2015;Kullen et al, 2002Kullen et al, , 2015. Finally, polar cap arcs have also been identified as the poleward edge of a thickened plasma sheet in the dawn and/or dusk sectors (Meng, 1981;Newell et al, 2009), that is, at the polar cap boundary of the HCAs, the subject of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies of the distribution of FTE signatures in the ionosphere [e.g., Lockwood and Davis, 1996;Provan et al, 1999;Milan et al, 2000;Wild et al, 2005;Fear et al, 2008Fear et al, , 2009Fear et al, , 2012Carter et al, 2015] have demonstrated that reconnection signatures can be observed over a wide range of magnetic local times (MLT) and that there appears to be an IMF B Y control of the location. Such studies have also shown that the FTE signatures can differ considerably in local time extent, from small scales of order a few 100 km [e.g., Oksavik et al, 2004Oksavik et al, , 2005 to larger scales encompassing 4-5 h of MLT [e.g., Lockwood et al, 1990].…”
Section: 1002/2015ja022012mentioning
confidence: 98%
“…Northern Hemisphere summer is taken for all values that occur during May, June, and July, and winter results compose of values that occur in November, December, and January. A similar method was employed in Carter et al (2015) to parameterize FACs, as obtained from the Active Magnetosphere and Planetary Electrodynamic Response Experiment (AMPERE). We examine the parameterized SSUSI products with respect to the FACs.…”
Section: Datamentioning
confidence: 99%